Ouvir e falar: o procedimento estruturado em MEI no ensino de bebês - Silva, Giulia Gomes da (2020)
The studies presented in this dissertation addressed to investigate teaching procedures to produce the shared control of stimuli to the repertoires of selection and tact to babies with ages between 24 and 29 months. For this reason, we conducted a systematic review of the literature, which resulted in the study 1. The objective of this study was to identify in the research reports the procedures that were structured in Multiple Exemplar Instruction (MEI), for teaching the behaviors of listeners and speakers of children up to 50 months of age, which resulted in emerging tact. A systematic review was conducted in accordance with the requirements of the protocol PRISMA. The searches were conducted in Databases EBSCO; ERIC; PubMED, SCOPUS; Pepsic; LILACS; SciELO; Google Scholar, without a cut of period of publication. The descriptors used were: "Instrução com Múltiplos Exemplares” and “Multiple Exemplar Instruction”. The searches resulted in the recovery of a total of 498 studies. Of these, only 4 were selected for analysis. Two studies have taught tasks of Matching-To-Sample auditory-visual, MTS visual-visual with instruction and tact pure structured in MEI. The other two studies have taught the same tasks by adding the tact impure in the structure of MEI. In relation to the procedures and results, the average number of blocks required for teaching structured in MEI was different for each study, even for those who taught the same tasks. It seems that the variable that influenced the results was the programd instruction before exposure to teaching structured in MEI. The structures of teaching found in North American literature, resulted in adapting them to the line of research carried out in the Laboratório de Interação Social and for brazilians babies. That said, the study 2 had as aim to verify the effectiveness of teaching of tasks of selection and emission of tact employing the structured procedure in MEI on the emergence of operant tact for childrens up to 30 months. For this, an a experimental research was carried out with a multiple-probe design. Participated in the study, six children with ages between 24 to 29 months of age, four of them born at term and preterm infants. The research was developed in a school of public education. The instruments used in the survey and evaluation of the repertoire of entry of participants were the Operational Portage Inventory and the Denver II. The study had the following experimental steps: a) baseline with all sets; b) teaching listeners, performed with selection tasks for set 1; c) probe of the behavior of listeners, performed with selection tasks and the behavior of speaker, performed with the emission of the tact for all sets; d) teaching of tasks of tact emission and selection structured in MEI for set 2; e) probe of the behavior of listeners, performed with selection tasks and the behavior of speaker, performed with the emission of the tact for all sets; f) teaching tasks of selection and emission of tact structured in MEI for set 3; g) probe of listener behavior, performed with selection tasks and speaker behavior, performed with the emission of tact for all sets; h) categorization probe. Three participants reached the finale of the study. Two of them produced emerging tact for 83.3% of new stimuli and were exposed only to teaching structured in MEI for set 2. One participant issued 66.6% of emerging tact for new stimuli. In relation the categorization probes, two participants responded correctly and grouped the stimuli according to the categories. The teaching of tasks of selection and emission of tact structured in MEI showed good results for 29-month-old babies to produce derived relationships of tact. Two studies demonstrate that the teaching structured in MEI seems to be a good way for the integration of two repertories for the babies.